2017
DOI: 10.1039/c7ra11748e
|View full text |Cite
|
Sign up to set email alerts
|

Holistic and dynamic metabolic alterations of traditional Chinese medicine syndrome in a toxic heat and blood stasis syndrome rat model

Abstract: Metabonomic analysis has been widely used in the study of traditional Chinese medicine (TCM) syndromes.In this paper, dynamic changes of the metabolic network during the evolution of a syndrome based on the toxic heat and blood stasis syndrome (THBSS) rat model have been elucidated for the first time. It was found that the metabolic trajectories could characterize three stages during THBSS evolution: the metabolic disturbance at 2-5 h, 8-12 h and 24-48 h could reflect the status of the excessive heat and littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Additionally, glycine can generate serine, which can be converted into glucose for energy (Wheeler et al, 1999). We previously noted that energy is needed for the proliferation of inflammatory cells during this stage (Xu et al, 2017). Therefore, we considered that the elevation of glycine and serine in PRR-treated group A observed in the present study may be associated with preventing the expression of inflammatory cytokines.…”
Section: Regulation Of Amino Acid Metabolismmentioning
confidence: 70%
See 4 more Smart Citations
“…Additionally, glycine can generate serine, which can be converted into glucose for energy (Wheeler et al, 1999). We previously noted that energy is needed for the proliferation of inflammatory cells during this stage (Xu et al, 2017). Therefore, we considered that the elevation of glycine and serine in PRR-treated group A observed in the present study may be associated with preventing the expression of inflammatory cytokines.…”
Section: Regulation Of Amino Acid Metabolismmentioning
confidence: 70%
“…injection of LPS (50 μg/kg). The time point of i. v. LPS administration was 0 h. In our previous study, we found that during 2-5 h, the rats were in the EHLBS stage and reached the BS stage after 24 h (Xu et al, 2017). Therefore, for the EHLBS-related studies, the freeze-dried PRR powder was dissolved in pure water and administered intragastrically (1.68 g/kg, at 10:00 a.m., once daily) to the rats in PRR-treated group A from the first day to the third day.…”
Section: Animal Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations